Evolution of a prenatal genetic clinic—A 10‐year cohort study. (21st February 2020) - Mone, Fionnuala; O'Connor, Clare; Hamilton, Susan; Quinlan‐Jones, Elizabeth; Allen, Stephanie; Marton, Tamas; Williams, Denise; Kilby, Mark D.
Abstract: OBJECTIVE: To (a) evaluate the proportion of women where a unifying genetic diagnosis was obtained following assessment of an observed pattern of fetal anomalies and (b) assess trends in genetic testing in a joint fetal‐medicine genetic clinic. METHOD: Retrospective cohort study of all women attending the clinic. Outcomes included (a) indication for referral, (b) genetic test performed and (c) diagnoses obtained. RESULTS: From 2008 to 2019, 256 patients were referred and reviewed, of which 23% (n = 59) were consanguineous. The main indication for referral was the observed pattern of fetal anomalies. Over 10 years, the number of patients reviewed increased from 11 to 35 per annum. A unifying genetic diagnosis was obtained in 43.2% (n = 79/183), the majority of which were diagnosed prenatally (50.6% [n = 40/79]). The main investigation(s) that was the ultimate diagnostic test was targeted gene panel sequencing 34.2% (n = 27/79), with this and exome sequencing becoming the dominant genetic test by 2019. Pregnancies reviewed due to an abnormal karyotype or microarray decreased as an indication for referral during the study period (21.6% [n = 16/74] 2008‐2012 vs 16.5% [n = 30/182] in 2012‐2019). CONCLUSION: A prenatal genetic clinic with a structured multi‐disciplinary team approach may be successful in obtaining a unifying prenatal genetic diagnosis.